1997
DOI: 10.1111/j.1600-0560.1997.tb01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of muscarinic acetylcholine receptors in primary and metastatic malignant melanomas

Abstract: In embryos morphogenetically active cells transiently express the cholinergic system comprising cholinesterase activity and muscarinic acetylcholine receptors. Malignant melanomas develop from melanocytes, which are derived from the neural crest. Neural crest cells express the embryonic muscarinic system during migration. Using the monoclonal antibody M35, we now show that normal melanocytes carry no muscarinic receptors, whereas malignant melanoma cells express them again. In primary melanomas and metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…For example, it is known that dermal nevus cells morphologically resemble Schwann cells of the peripheral nervous system and express Schwann cell-related antigens (29). Invasive primary melanoma cells, on the other hand, adopt a phenotype that includes the expression of certain proteins typical of neurons rather than Schwann cells (31)(32)(33)(34). Consistent with this notion, we showed that MAP2 is expressed more frequently in invasive primary melanomas than in early non-invasive primary melanomas both in vivo (5) and in vitro (WM35 versus WM115 shown in this study).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that dermal nevus cells morphologically resemble Schwann cells of the peripheral nervous system and express Schwann cell-related antigens (29). Invasive primary melanoma cells, on the other hand, adopt a phenotype that includes the expression of certain proteins typical of neurons rather than Schwann cells (31)(32)(33)(34). Consistent with this notion, we showed that MAP2 is expressed more frequently in invasive primary melanomas than in early non-invasive primary melanomas both in vivo (5) and in vitro (WM35 versus WM115 shown in this study).…”
Section: Discussionmentioning
confidence: 99%
“…The choline that is generated by acetylcholinesterase is transported back into the nerve ending by high-affinity transporters, where it can be reused for ACh synthesis. ACh has been detected in autonomic nerve fibers (725), melanocytes (369,466), and keratinocytes of human skin (289) as well as in lymphocytes (57,677). It regulates different activities in keratinocytes, such as proliferation, adhesion, migration, and differentiation.…”
Section: A Ach and Receptorsmentioning
confidence: 99%
“…The skin is one such organ, targeted by many challenges that invoke an inflammatory response to maintain homeostasis and integrity. In the skin, the expression of ACh and its receptors has been found in nerve fibers, keratinocytes, melanocytes, and in cells of the immune system, such as mast cells and lymphocytes (Bering et al 1987;Grando et al 1993; Iyengar 575028J HCXXX10.1369/0022155415575028Rommel et alSuitable acetylcholine receptor antibodies research-article2015 1989; Lammerding-Koppel et al 1997;Richman and Arnason 1979;Schmelz et al 2000). Furthermore, human keratinocytes have been shown to express ACh synthesizing and hydrolyzing enzymes, namely choline acetyltransferase (ChAT) and acetylcholinesterase (AChE) (Grando 1997).…”
Section: Introductionmentioning
confidence: 99%